ANALISIS MANAJEMEN LABA USAHA PADA KEDAI KOPI DI KABUPATEN MANOKWARI, PAPUA BARAT - Sandi, Juniandini Tiara; Nurwidianto, Nurwidianto; Sudarwadi, Dirarini Sudarwadi (Politeknik Negeri Ambon, 2025)
Introduction: This study aims to see how the financial attitude of coffee shop business owners, as well as how to manage the profits of coffee shop business owners. This type of research uses qualitative research with descriptive explanations. Methods: The method used in the sample is cluster sampling. The population in this study consists of coffee shops; the sample comprises 5 coffee shops. The types of data used are primary data and secondary data. Data collection techniques use observation, interviews, and literature studies.Results: The results of this study show that: (1) The financial attitude possessed by the coffee shop business owner is said to be right, able to plan sound finances, able to separate business money and personal money, set aside money to save, and make a record of money in and out of business. Coffee shop owners can also manage risks effectively and establish businesses using their own capital and borrowed funds. (2) The management of the coffee shop business profits carried out by the owner has made and compiled business profit targets regarding the amount of profit, has made a budget for the costs that will be incurred in the business. The shop owner has determined the selling price by looking at the cost of raw materials and looking at market conditions. Has recorded and routinely checked every business income and expenses, has prepared a plan to open a new branch and renovate the location by making good planning, has prepared solutions to avoid risks that will occur in the future, has succeeded in setting aside the proceeds of savings for capital turnover, and other business needs. Keywords: Financial Attitude, Profit Management, Coffee Shop, West Papua